Peran Kader dalam Pemantauan Pertumbuhan Balita Bawah Garis Merah - Yunita, Jasrida; Nurlisis, Nurlisis (Jurnal Kesehatan Komunitas, 2018)
Undernourished children can manifest in several degrees: under or severe. Cadres play a critical function in tracking children's development. This research aimed to gather comprehensive data regarding the function of cadres in monitoring undernourished children. The study was conducted at the Umban Sari Public Health Center, using a qualitative methodology. Seven informants were chosen by purposive sampling. An extensive interview guide, recorders, cameras, and field notes were used as research instruments to capture all of the data in the field. Through observations and interviews, data were gathered. Triangulation techniques were used to validate the data. The results showed that cadres have a considerable function as communicators between the community and health professionals; in addition to being active in the planning and implementation of activities on the day of Posyandu for integrated services; however other than the integrated services, there was still limited role: only to greet mothers on their way to Posyandu; visitation activities conducted by the health officers accompanied by cadres when the toddler was first detected undernutrition and toddlers did not attend two consecutive months; provided guidance to the public was still not maximized; and cadres were still less active in counseling. t is recommended that cadres hold frequent meetings and training sessions, delegate authority to them beyond the integrated services, develop dietary guidelines for families, and distribute children's health literature.